APPLICATION OF VIRTUAL SOCIAL NETWORKS FOR PURPOSES OF GENERAL SECONDARY EDUCATION - Iatsyshyn, А.В. (Journal of Information Technologies in Education (ITE), 2015)
The rapid development of information technology, which happens all the time, helps to activate the process of virtualization world education and calls for the revision and introduction of modern methods and tools in the educational process. In the information society becomes wider network of social services and as a result of the spread of virtual education, training and social networks that bring people together around common interests or values to form a particular social group users by meeting their needs. Virtual social networks are a powerful tool to maintain communication of millions of people on the Internet, as some social communities already have hundreds of millions of registered users.Believe that consideration of the possibilities of virtual social networks in the coming years is relevant, because it opens prospects for using them for training purposes in its entirety. In the article the services offered by virtual social networks are considered; the possibilities of using of these services as the tools of educational process organization are defined; the positive and negative features of virtual social networks are outlined; the opportunities and ways of using of virtual social networks in purposes of secondary education are analyzed.